2017
DOI: 10.1016/j.scitotenv.2017.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients in one-carbon metabolism and urinary arsenic methylation in the National Health and Nutrition Examination Survey (NHANES) 2003–2004

Abstract: Exposure to inorganic arsenic (inAs), a potent toxicant, occurs primarily through ingestion of food and water. The efficiency with which it is methylated to mono and dimethyl arsenicals (MMA and DMA) affects toxicity. Folate, vitamins B12 and B6 are required for 1C metabolism, and studies have found that higher levels of these nutrients increase methylation capacity and are associated with protection against adverse health effects from inAs, especially in undernourished populations. Our aim was to determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 65 publications
0
37
0
Order By: Relevance
“…A growing body of evidence shows that DNA methylation plays an important role in the progression of cancers ( 3 ). DNA methylation requires a methyl donor, which is mainly provided by one-carbon metabolism (OCM) ( 4 , 5 ). S-adenosylmethionine (SAM), the activated form of methionine, serves as the most important methyl donor.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence shows that DNA methylation plays an important role in the progression of cancers ( 3 ). DNA methylation requires a methyl donor, which is mainly provided by one-carbon metabolism (OCM) ( 4 , 5 ). S-adenosylmethionine (SAM), the activated form of methionine, serves as the most important methyl donor.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, As can also have different excretion patterns in participants of the same group (intra-individual variability; inter-individual variability) [52] or between groups [28,51]. However, the literature reports that many factors influence arsenic metabolism and condition its efficiency, including genetic factors (example: polymorphisms of the arsenite methyltransferase), metabolic capacity, sex, hormonal mechanisms, nutritional status, and diet [28,48,52,53].…”
Section: Uas Concentrationmentioning
confidence: 99%
“…However, nowadays the importance of consuming these potential sources of phytochemicals such as quelites has been forgotten, which could be used as alternative therapies to reduce the effects of various pathophysiological conditions, including As toxicity [21]. Some studies on populations exposed to As have reported that the consumption of natural supplements or foods rich in bioactive compounds improve the processes of methylation and increase the levels of excretion of As, promoting an efficient recovery process [28,42,53,56]. On the other hand, nutritional deficiencies due to low consumption of micronutrients contribute to increasing the risk of arsenic-induced skin lesions [57].…”
Section: Uas Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than As3MT , SNPs in N6AMT1, GSTO , and GLRX , as well as some genes that may not be closely involved in the arsenic methylation process, are associated with the concentrations or percentages of urinary arsenic metabolites ( Antonelli et al, 2014 ; Beebe-Dimmer et al, 2012 ; Gao et al, 2015 ; Harari et al, 2013 ). For example, one-carbon metabolism (OCM) is a biochemical pathway that is able to provide methyl groups for arsenic methylation, and related nutritional status is reported associated with arsenic methylation efficiency in pregnant and non-pregnant cohorts ( Bozack et al, 2018 ; Kurzius-Spencer et al, 2017 ; Laine et al, 2018 ). Methylenetetrahydrofolate reductase (encoded by MTHFR ) is an important enzyme involved in OCM, and plays a role in the supplement of SAM in arsenic metabolism ( Chung et al, 2010 ; Wlodarczyk et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%